The Impact of Changes in External and Internal Factors on Financial Performance and Stock Returns of Coal Companies - Ade Arief Komara; Bonar M. Sinaga; Trias Andati (School of Business, Bogor Agricultural University (SB-IPB), 2019)
This study aimed to investigate the impact of external and internal factors on financial performance and stock return of coal companies listed in the Indonesia stock exchange. The simultaneous equations model was constructed and estimated using the 2SLS (Two-Stage Least Squares) method. The annual data panel of seven coal mining companies from 2012 up to 2017 were utilized. The results of the model validation showed that 76.92% of the variables have U-Theil values below 0.5 and 23.1%, the values are above 0.5, which means that the predictive values of endogenous variables were good enough for simulation models. Based on the modeling and simulation results, we concluded that coal prices, the rupiah exchange rate, China's GDP were external factors that influence the amount of coal export sales. The exchange rate of the dollar against the rupiah was an external factor that has a dominant impact on the value of MVA and the stock returns. Coal price was external factors that have a dominant impact on financial performance (EBIT, PAT, and EVA). Reduction of revenue costs, operational costs, and general administration was an internal factor that could be carried out to reduce the impact on financial performance in case of changes in external factors, but this did not affect the stock return and MVA.Keywords: Coal, EBIT, EVA, MVA, ReturnAbstrak: Penelitian ini bertujuan mengetahui dampak perubahan faktor eksternal dan internal terhadap kinerja keuangan dan return saham perusahaan batubara yang terdaftar di bursa efek Indonesia. Model persamaan simultan dibangun dan diestimasi menggunakan metode 2SLS (Two Stage Least Squares). Data panel tujuh perusahaan pertambangan batubara tahun 2012–2017 digunakan pada penelitian ini. Hasil validasi model yang dibangun menunjukkan bahwa 76,92% dari variabel mempunyai nilai U-Theil dibawah 0,5 dan 23,1% nilainya diatas 0,5, yang berarti bahwa nilai prediksi variabel endogen cukup baik digunakan untuk simulasi model. Berdasarkan pemodelan dan hasil simulasi dapat disimpulkan bahwa harga batubara, nilai tukar rupiah, GDP Tiongkok merupakan faktor-faktor eksternal yang mempengaruhi jumlah penjualan batubara ekspor. Nilai tukar dollar terhadap rupiah merupakan faktor eksternal yang berdampak dominan terhadap nilai MVA dan nilai return saham. Harga batubara merupakan faktor eksternal yang berdampak dominan terhadap kinerja keuangan (EBIT,PAT dan EVA). Pengurangan biaya pendapatan, biaya operasional dan administrasi umum merupakan satu-satunya faktor internal yang bisa dilakukan untuk mengurangi dampak terhadap kinerja keuangan jika terjadi perubahan faktor eksternal, namun hal itu tidak berdampak terhadap return saham dan MVA. Kata kunci: Batubara, EBIT, EVA,MVA, Return